Invasion of an exotic annual forb affects grass‐feeding termites in a semi‐arid woodland. (16th May 2022) - Val, James; Eldridge, David J.
Abstract: Invasive plants are known to have dramatic and generally negative effects on ecosystems. The rapid spread and naturalization of Carrichtera annua (wards weed) across large areas of southern Australia has been widely reported, but its effects on biodiversity and ecosystem functions are poorly known. We examined the effects of Carrichtera on grass‐feeding termites Drepanotermes spp. and hypothesized that increasing cover of Carrichtera would reduce termite abundance, which we assessed using the density of their above‐ground pavements as a proxy for density. Our study was conducted at two spatial scales to explore (i) potential effects of Carrichtera invasion under variable intensities of grazing and (ii) differences between invaded and uninvaded sites at a long‐ungrazed conservation reserve. Increasing cover of Carrichtera was associated with a greater density of pavements, both under grazed conditions and within the conservation reserve. However, increasing grazing intensity tended to be associated with reduced pavement density and size, through indirect reductions in plant biomass. Greater cover of Carrichtera was associated with declines in the cover of native plants and biocrusts, but not native plant richness. Pavement size tended to decline with increasing pavement density. Under conservation, Carrichtera sites supported more pavements, but densities declined markedly in drought years. The lower resilience to droughts and the fact that pavements in Carrichtera ‐invaded sites tended to be less cemented and contain more ants, suggest that invasion by Carrichtera may have long‐term functional implications for processes mediated by termites. Increasingly, drier climates in southern Australia may exacerbate reductions in ecosystem functions given the pivotal role played by termites in dryland food webs and ecosystem functions.